2016
DOI: 10.1021/acs.chemrev.6b00365
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman Scattering with Dielectrics

Abstract: Dielectrics represent a new frontier for surface-enhanced Raman scattering. They can serve as either a complement or an alternative to conventional, metal-based SERS, offering key advantages in terms of low invasiveness, reproducibility, versatility, and recyclability. In comparison to metals, dielectric systems and, in particular, semiconductors are characterized by a much greater variety of parameters and properties that can be tailored to achieve enhanced Raman scattering or related effects. Light-trapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
459
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 542 publications
(464 citation statements)
references
References 409 publications
(729 reference statements)
4
459
0
1
Order By: Relevance
“…[4,11] However, their developments are often limited by their increasingly exposed shortcomings, such as the low number of varieties, poor biocompatibility, easy agglomeration, secondary pollution, and nonreusability. [13,14] Additionally, the high selectivity of semiconductor SERS substrates to probed molecules can also become a unique advantage when distinguishing a specific molecule from the complex environment with many other molecules. Although their enhancement effect is usually low, between 10-10 5 , and the problem of their unclear and controversial enhancement mechanism has persisted, semiconductors can still become one of the most promising candidate SERS substrate materials due to their rich variety, excellent biocompatibility, and useful versatility.…”
Section: Introductionmentioning
confidence: 99%
“…[4,11] However, their developments are often limited by their increasingly exposed shortcomings, such as the low number of varieties, poor biocompatibility, easy agglomeration, secondary pollution, and nonreusability. [13,14] Additionally, the high selectivity of semiconductor SERS substrates to probed molecules can also become a unique advantage when distinguishing a specific molecule from the complex environment with many other molecules. Although their enhancement effect is usually low, between 10-10 5 , and the problem of their unclear and controversial enhancement mechanism has persisted, semiconductors can still become one of the most promising candidate SERS substrate materials due to their rich variety, excellent biocompatibility, and useful versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that TiO 2 represents one of the most promising materials for Surface Enhanced Raman Scattering (SERS), because of its high refractive index, versatile surface functionalization, synergistic coupling to plasmonic nanoparticles, cocatalysts, and so on. Thus it could be used to analyze and monitor the process of photocatalytic degradation [7,8,9]. Meanwhile, TiO 2 with its extraordinary chemical stability, environmentally friendly, and biocompatible characteristics, has been intensively investigated as a benchmark material for many photocatalytic reactions [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1 This emerging interest stems from several factors. One is the possibility to exploit a rich variety of opportunities to tune the Raman response.…”
Section: Resonant Laser Printingmentioning
confidence: 99%